Potential forensic issues in overseas travellers exposed to local herbal products. (November 2018) - Farrington, Rachael; Musgrave, Ian; Nash, Christine; Byard, Roger W.
Highlights: Tourism is exposing more travellers to traditional medicinal products. The exact composition of many of these medications is unknown. There is a possibility of adulteration with potentially harmful pharmaceutical drugs. These substances should be checked at autopsy in recently returned travellers.